2010
DOI: 10.1002/pros.21298
|View full text |Cite
|
Sign up to set email alerts
|

Selenoprotein‐P is down‐regulated in prostate cancer, which results in lack of protection against oxidative damage

Abstract: Levels of SepP in prostate cells determine basal ROS levels and sensitivity to H(2)O(2)-induced cytotoxicity. Deregulation of SepP during prostate carcinogenesis may increase free radicals, thus promoting tumor development and de-differentiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 53 publications
3
24
0
Order By: Relevance
“…A recent study showed a downregulation of SepP in PCa which leads to decreased cellular protection against oxidative damage [24]. Our data demonstrated that compared to control, a marked up-regulation of SepP occurs in all the treatment groups except MSA (Figure 6B).…”
Section: Resultssupporting
confidence: 63%
See 2 more Smart Citations
“…A recent study showed a downregulation of SepP in PCa which leads to decreased cellular protection against oxidative damage [24]. Our data demonstrated that compared to control, a marked up-regulation of SepP occurs in all the treatment groups except MSA (Figure 6B).…”
Section: Resultssupporting
confidence: 63%
“…A recent study demonstrated that SepP is reduced in 60.8% of human prostate tumors as compared to benign prostates [24]. Our data shows marked increase in SepP expression in γT1 and MSA + γT1 groups, favoring lower dose of γT over a higher dose.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…serum Se and selenoprotein P (SePP) concentrations are reduced in prostate cancer patients and this is correlated with disease severity [13]. This in turn could reduce selenoprotein expression and associated anti-oxidant defense resulting in increased oxidative damage leading to prostate cancer progression [14].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of the prostate-specific transglutaminase in PCa has been recently reported as a potential antitumour target ). Yet another important finding from this study were proteins reported to be implicated as potential cancer chemoprevention targets also affiliated with poor nutritional status and metabolic syndrome disease (Das et al, 2011;De Nunzio et al, 2011;DeMarzo et al, 2003;Dong, Zhang, Hawthorn, Ganther, & Ip, 2003;Gonzalez-Moreno et al, 2011;Jeronimo et al, 2004;J. Kim et al, 2005;Kuemmerle et al, 2011;Menendez & Lupu, 2007;Nelson et al, 2005;Oh et al, 2006;Sytkowski, Gao, Feldman, & Chen, 2005;Toki et al, 2010;Tsavachidou et al, 2009;Walsh, 2010;C.…”
Section: Prostate Cancer 41 the Quantitative Proteomic Profiling Of mentioning
confidence: 70%